Pengaruh Perendaman dalam Larutan Kapur dan Lama Penyimpanan Terhadap Kualitas Telur Asin - Sri Hastuti (AGROINTEK, 2010)
The objective of the study was to learn the effect of lime duration and storage durationon quality of salted egg. The research was a factorial experiment (2x4) using Randomized BlockDesign with three replication. The first factor was preservation of two levels, i.e. : withoutsoaking in lime solution (P0) and with soaking in lime solution (P1). The second factor wasstorage duration, i.e ; 0 (L1), 12 (L2), 24 (L3), and 36 (L4) days. The variable measured were themicrobial load, protein content and organoleptic properties, i.e : the colour, flavor, taste andtexture of salted egg. Data were subjected to analysis of variance followed by Duncan MultipleRange Test (DMRT). The conclusion was that the interaction between soaking in lime solutionand storage duration had no different effect on protein content, microbial load, flavour and tastebut it had different effect on texture and colour of salted egg. The soaking in lime solution gavea lower result of microbial load i.e : 6,55x107 cfu/g but the organoleptic quality on texture,colour and flavour of salted egg gave a lower degree of preference score by panelist. It issuggested to keep salted egg preserved with lime solution at room temperature not more than 24days to produce good quality salted egg base on protein content, microbial load, flavor and taste.